Factors That Affect Employee Performance at The Manpower and Transmigration Office of West Kutai Regency - Edison Suanto; Ida Bagus Made Agung Dwijatenaya; Musmuliadi Musmuliadi (Journal Research of Social Science, Economics, and Management, 2022)
The development of science and technology in the last decade is amazing. This study aims to determine and analyze the factors of discipline, work environment, coordination and employee welfare that have a partial effect on employee performance at the Department of Manpower and Transmigration of West Kutai Regency and to find out how factors influence simultaneously on employee performance at the Department of Manpower. and Transmigration of West Kutai Regency. The design of this study was conducted using a qualitative and quantitative descriptive approach. This type of research is a survey, namely analyzing the facts and data needed to support the research discussion, in solving and answering the main problems proposed, namely: analyzing the performance of employees at the Manpower and Transmigration Office of West Kutai Regency. Based on the results of the analysis described previously, it shows that the level of employee performance at the Manpower and Transmigration Office of West Kutai Regency is significantly influenced by discipline factors, work environment, coordination, and employee welfare. Meanwhile, the independent variable that has the most dominant influence is the welfare variable.